A Narrative Inquiry of Student’s Public Speaking Ability by Bilingual (English & Arabic) at Boarding School of the Al-Mashduqiyah Kraksaan - Risqiyah, Arifatur; Wisudaningsih, Endah Tri; Fatmawati, Ririn (Universitas Nusantara PGRI Kediri, 2023)
A narrative inquiry of students' public speaking, ability using bilingual, English, and Arabic. This research aims to explore the story of the experience of public speaking, students during students studying at Al-Mashduqiyah. More specifically, the study aimed to understand the difficulties and coping strategies that students face when speaking in public using a foreign language. The method used by the qualitative approach is narrative inquiry. A Junior High student participated in the study. To collect data valid information researcher use questionnaires, interviews, dairy, and documentation obtained from participants and a teacher. As a result, this narrative investigation shows the problems of public speaking in two languages, individual factors, and implementing them into public speaking. To overcome difficulties in public speaking, participants apply strategies with repetition and habituation. This study shows that the mastery of language, accent, and manner of delivery is important because it affects the audience's understanding of the communication.